Problem Based Learning dengan Metode Gallery Walk untuk Mengatasi Rendahnya Kemampuan Pemahaman Konsep Matematika - Pebriani, Yuni (Postulat : Jurnal Inovasi Pendidikan Matematika, 2022)
This study aims to overcome the low ability to understand students' mathematical concepts in statistical material, especially the size of group data placements through learning with problem-based learning models using the gallery walk method. The research design used is a quantitative descriptive research design. This includes the stages of data collection, processing data, and interpreting the results. This research involved the subject, namely, students of class XII MIPA 1 at SMA Negeri 1 Tanjungsiang. The instruments used included diagnostic tests, formative tests, summative tests, teaching module implementation observation sheets, and teacher observation sheets. The results showed that the average score of the formative test at the first and second meetings was 71.5 in the medium category and 82.5 in the high category respectively. In addition, as a whole, the student achievement on indicators of understanding the concept as much as 78% is in the medium category. As well as the achievement of the learning objectives of students in the material size of the location of the group data of 78.28, it is in the category that has reached completeness, no need for remedial. Keywords: Concept Understanding, Gallery Walk, Problem Based Learning